The Dependence of Electrochemical Behavior and Discharge Performance on the Zn/Gd Ratio of Mg-Li-Zn-Gd Anodes for Mg-Air Batteries - Siqi Yin; Ningyuan Wang; Haoxuan Han; Zichen Liu; Guangzong Zhang; Renguo Guan (Metals)
In this study, the electrochemical performance and discharge behavior of Mg-Li-Zn-Gd alloys with α-Mg and β-Li-based anode material are investigated, with the aim to improve the anode performance of Mg-air batteries. The experimental anode alloys with detailed Mg-8Li-xZn-yGd (x = 1, 2, 3; y = 1, 2, 3 wt.%) components are prepared, and extrusion deformation is carried out on these alloys. Simultaneously, scanning electron microscope (SEM), X-ray diffractometer (XRD), electrochemical workstation, and constant current discharge systems are applied for microstructure characterization, corrosion, and discharge performance testing. The results show that the experimental alloys are composed of an α-Mg and β-Li dual matrix, with W-Mg3Gd2Zn3, Mg3Gd, and MgLiZn second phases. Meanwhile, extrusion deformation promotes the recrystallization process through the particle-induced nucleation mechanism. The corrosion resistance is improved with the increasing Zn/Gd ratio, and the extruded Mg-8Li-2Zn-1Gd (LZG821) alloy exhibits the optimum corrosion resistance, with a corrosion rate of 0.493 mm·year−1. In addition, the extruded Mg-8Li-1Zn-1Gd (LZG811) alloy has the optimal discharge performance, with a discharge specific capacity of 1371.04 mA·g−1 at a current density of 40 mA∙cm−2, and its anode efficiency reaches nearly 70%. The poorer discharge properties of the Mg-8Li-2Zn-1Gd (LZG821) and Mg-8Li-2Zn-3Gd (LZG823) alloys are attributed to their refined grains, which could bring severe intergranular corrosion while increasing the grain boundary density.